Potensi Daun dari Enam Jenis Tumbuhan sebagai Pewarna Alami untuk Tekstil: The Leaf Potential of Six Plant Species as Natural Dyes for Textile - Ariyanti, Nunik Sri; Hayati, Neng Sri; Hadisunarso (Jurnal Sumberdaya Hayati, 2023)
The use of natural dyes for textile have advantages since they are enviromentally friendly. This study aims to analyzed the potential use of six plant species as natural dyes for textiles. This research used leaves of pucuk merah (Syzygium oleana), cinnamon (Cinnamomum burnamii), avocado (Persea americana), jakaranda (Jacaranda mimosifolia), eucalyptus (Eucalyptus sp.), and lanang (Oroxylum indicum); three types of mordant (alum, ferrous sulphate, lime); and three types of fabrics (silk, combed cotton, primisima cotton). The research stages included extracting dyes from the leaves and dyeing fabrics that had previously been treated with mordant. The potential dye was analyzed based on the color and its stability on fabrics. The colors were identified using RGB (Red Green Blue) Color Chart Reader. Color stability was measured based on the fastness test against washing process referring to SNI ISO 105-C06-2010. The application of dyes on different types of fabrics which was treated with different mordants yield color variations. In addition, mordant has a good effect on color fastness. All extract showed the best color and fastness on silk fabric treated with ferous sulphate. The plant observed in this study have potential use as textile dyes, but it is necessary to consider the type of fabric and mordant to make the best results.